Turkey and Europe data comparison in terms of the course of the COVID-19 pandemic and health expenses - Feruza Turan Sönmez; Cemil Işık Sönmez (SERNEV, 2022)
Introduction: The COVID-19 pandemic has affected the entire world and has been a challenge to the health prospects of the nations infected. The elderly population of the nations and parameters like the countries' health system and the allocation of budget to health are critical factors for explaining the epidemic's development with different mortality rates in various countries. The purpose of the study was to assess the characteristics of the Turkish population, COVID cases, the progression of diseases, and health expenditures compared to those in Europe.Methods: For this study, we used the following databases: the Worldometer digital database, the database of the Organization for Economic Cooperation and Development, and the Turkish National Databases on Economic and Finance references, such as the Turkish National Strategy and Budget Presidency and the database of the Turkish Statistical Institute. The data was for the date 15.12.2021 and the general annual for 2020.Results: By the investigation date as of 15/12/2021, the total number of COVID-19 cases was 9209740 in Turkey and 81556853 in the European Union countries. The incidence of the disease was 107.500 in Turkey and 135.525 in Europe. While the total change/ increase in last-week-new cases was -5% and 8% in Turkey and Europe, respectively, the real change/ increase in last-week-deaths was -1% to -8% in Turkey and Europe. The number of COVID screening tests per one million population was higher in Europe (1.343.256 to 8.790.27 in Turkey and Europe, respectively). The GDP and health expenditure per capita were distinctly higher in Europe.Conclusion: The fact that there is a higher percentage of elderly residents in European countries than in Turkey, that the number of new cases detected every week is higher, and that the death rate and the gradual decline in cases are linked to the large share of health expenditures distributed by nations for the fight against the disease.